Peranan Teknologi dalam Pembelajaran untuk Membentuk Karakter dan Skill Peserta Didik Abad 21 - Andromeda Valentino Sinaga (Departement of Mathematics Education, 2023)
The role of technological developments in learning has such a big impact. The existence of technology provides opportunities to broaden and enrich students' learning experiences. Technological developments have positive and negative impacts and provide challenges, especially in education. 21st-century learning requires students to have the characters and skills that are relevant to the digital era so that students will be ready to enter the industrial world. For this reason, in 21st-century learning, it is necessary to familiarize 21st-century skills, namely 4C, which includes Communication, Collaboration, Critical Thinking and Problem Solving, and Creative and Innovative. Achieving 21st-century skills can be done by improving the quality of learning, and the role of educators in implementing 21st-century learning is very important to create a better future for students. In addition, teachers must also have the latest skills and innovations in dealing with 21st-century learning.